Jacques Lacan / Tr. by David Macey - "Lemaire, Anika" (London, 1977)
The book 'Jacques Lacan ' emphasize on the subject of Psychoanalysis and the Subject of Literature (Transitions)
Keywords: "Lacan, Jacques"